Antimicrobial resistance in fecal flora: longitudinal community-based surveillance of children from urban Mexico. - Calva, J J (1996)
We assessed the colonization patterns, over time, of three sentinel drug-resistant enteric bacterial genera in samples from a cohort of 20 healthy small children in a periurban community in Mexico. The children were monitored during a 13-week period by means of weekly home visits and examinations of stool collections. These specimens were tested for the presence of Escherichia coli, Klebsiella species, and Shigella species resistant to one or more of seven antimicrobial agents. Ninety, 77, and 62% of the stool specimens had E. coli isolates resistant to ampicillin, trimethoprim, and tetracycline, respectively. Simultaneous resistance to more than one antibiotic by an E. coli isolate was observed in 88.5% of stool samples. Persistent fecal shedding of ampicillin-, trimethoprim-, and tetracycline-resistant E. coli occurred during the study period in the majority of children. We detected colonization by E. coli resistant to chloramphenicol, gentamicin, nitrofurantoin, or norfloxacin, as well as by Klebsiella species and Shigella species resistant to one of these antibiotics, in fewer children and for shorter periods. These data suggest the common and persistent intestinal shedding of multidrug-resistant E. coli strains by small healthy children.